Pengaruh Pertumbuhan dan Hasil Tanaman Pakcoy Terhadap Perlakuan Pupuk dan Baris Tanam pada Lahan Kering Melalui Sistem Budidaya Vertikultur - Maria Inosensia Mali; Fulgensius Palbeno; Wilda Lumban Tobing; Deseriana Bria; Natalia Desi Djata Ndua; Azor Yulianus Tefa (Jurnal Agrotek Lestari, 2025)
This study was to determine the effect of N fertilizer and row planting intervals on the growth and yield of pak choi plants in vertical cultivation with fertigation in dry land. This research method used an experimental Split Plot Design (RPT) consisting of 2 factors, namely the main plot and sub-plot. The main plot consists of: Urea 0.75 g / L + POC 30 mL / L + BPN 7.5 mL / L, Urea 0.5 g / L + POC 20 mL / L + BPN 5 mL / L and Urea 0.25 g / L + POC 10 mL / L + BPN 2.5 mL / L. The sub-plot consists of: the first row, the second row and the third row. So that a combination of treatments of 9 treatments was obtained which was repeated 3 times so that a total of 27 treatment combinations were obtained. The results of the study showed that urea 0.75 g/L + POC 30 mL/L + BPN 7.5 mL/L in the second planting row was able to increase the growth and yield of pak choi plants in vertical cultivation systems with fertigation on dry land.Keywords: row planting, liquid organic fertilizer, nitrogen fixing bacteria, pakcoy